Manifestations II Indian art in the 20th century : 100 artists from the DAG collection - Delhi Art Gallery; Karode, Roobina; Jehangir Art Gallery (New Delhi Delhi Art Gallery, 2004)
Exhibited at the Jehangir Art Gallery, Mumbai, July 25th to 31st, 2004 and Delhi Art Gallery, New Delhi, August 9th to 21st, 2004; includes biographical sketches of contemporary Indian artists.
Keywords: Delhi Art Gallery -- Exhibitions; Jehangir Art Gallery -- Exhibitions; Art, Indic -- 20th century -- Exhibitions